Comparative efficacy of neuromodulation and structured exercise program on pain and muscle oxygenation in fibromyalgia patients: a randomized crossover study - Rubio-Zarapuz, Alejandro; Apolo-Arenas, María Dolores; Tornero-Aguilera, José Francisco; Parraca, Jose A.; Clemente-Suárez, Vicente Javier (Frontiers in Physiology, 2024)
Introduction: This study investigates the comparative efficacy of neuromodulation therapy using the EXOPULSE Mollii Suit and a structured exercise program in pain modulation and muscle oxygenation in Fibromyalgia patients. Methods: A randomized, crossover, longitudinal, and experimental study design was employed, involving 10 female Fibromyalgia patients. Participants were subjected to two distinct treatment modalities: neuromodulation therapy with the EXOPULSE Mollii Suit and a strength-based High-Intensity Interval Training (HIIT) exercise program, each conducted over 16 sessions. Outcome measures included pain severity, assessed using the Numeric Rating Scale (NRS), and muscle oxygenation variables measured via Near-Infrared Spectroscopy (NIRS). Results: Both interventions demonstrated significant reductions in NRS scores and improvements in muscle oxygenation. However, the exercise program yielded more pronounced long term basal adaptations in muscle oxygenation compared to the neuromodulation therapy. Discussion: The findings underscore the potential of integrating non-pharmacological treatments, particularly structured exercise programs, in managing Fibromyalgia. While neuromodulation therapy presents a viable alternative, the exercise regimen’s capacity to induce basal muscle oxygenation adaptations suggests its superiority in addressing the complex symptoms of Fibromyalgia. Furthermore, these therapeutic approaches may enhance patients’ vocational values and employability opportunities by improving their functional capabilities and overall quality of life.